1988
DOI: 10.1093/nar/16.24.11835
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of thehemXgene, the third member of the Uro operon ofEscherichia coliK12

Abstract: In a recent paper (1), we described the cloning and sequencing of the hemp gene, the second member of the Uro operon. Sequencing the DNA past the stop codon of the hemD gene revealed the presence of another ORF of at least

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…While this result is expected, given that the authors used TMHMM, a predictor of α-helices, to select potential TIMPs (see Green fluorescent protein (GFP) expression studies) before analysis, we note that the other more global study by Dr H. Mori and colleagues using GFP to determine protein subcellular localization ( http://ecoli.naist.jp/GFP/gfp_top.jsp ) also ranked highly in terms of ‘Agreement’ ( A =0.84), despite the fact that no bioinformatic prefiltering was seemingly used. Of the 471 ‘Membrane’ proteins (without specified status as TIMPs or TOMPs) analyzed by GFP in this study, we found that 395 of them (83%) are likely TIMPs based on the ‘Majority Consensus’, another 46 (10%) are predicted as cytoplasmic (although 10 contain one or two putative α-helices), one is predicted as OM and other as EC while the remaining 28 (5%) had no prediction, although Phobius predicted α-helices in 14, including the poorly characterized proteins HemY and HemX suggested to be a uroporphyrinogen III methylase ( Sasarman et al , 1988 ). This overlap of common hits between the GFP studies, bioinformatic predictors and knowledge databases provides strong evidence for both novel and corroborative TIMP annotations (see Table S1 for a detailed list), suggesting that an integrative approach can achieve high precision for detecting TIMPs (i.e.…”
Section: Deciphering the E Coli Cell-envelope Promentioning
confidence: 95%
“…While this result is expected, given that the authors used TMHMM, a predictor of α-helices, to select potential TIMPs (see Green fluorescent protein (GFP) expression studies) before analysis, we note that the other more global study by Dr H. Mori and colleagues using GFP to determine protein subcellular localization ( http://ecoli.naist.jp/GFP/gfp_top.jsp ) also ranked highly in terms of ‘Agreement’ ( A =0.84), despite the fact that no bioinformatic prefiltering was seemingly used. Of the 471 ‘Membrane’ proteins (without specified status as TIMPs or TOMPs) analyzed by GFP in this study, we found that 395 of them (83%) are likely TIMPs based on the ‘Majority Consensus’, another 46 (10%) are predicted as cytoplasmic (although 10 contain one or two putative α-helices), one is predicted as OM and other as EC while the remaining 28 (5%) had no prediction, although Phobius predicted α-helices in 14, including the poorly characterized proteins HemY and HemX suggested to be a uroporphyrinogen III methylase ( Sasarman et al , 1988 ). This overlap of common hits between the GFP studies, bioinformatic predictors and knowledge databases provides strong evidence for both novel and corroborative TIMP annotations (see Table S1 for a detailed list), suggesting that an integrative approach can achieve high precision for detecting TIMPs (i.e.…”
Section: Deciphering the E Coli Cell-envelope Promentioning
confidence: 95%
“…Urogen III methylase may be coded by hemX (47). Following cyaA, two potential ORF's overlap in opposite directions.…”
mentioning
confidence: 99%
“…This region has previously been found in other groups of bacteria (Sasarman et al . ; McNicholas et al . ).…”
Section: Resultsmentioning
confidence: 99%